Public and private tools to encourage FDI : the case of the Czech Republic and the Visegrad countries - Rodrigues, Ricardo Daniel Esteves (2016)
An important amount of capital inflows has been drawn to Central and Eastern European (CEE) countries. The process initiated in the first half of the nineteen nineties became particularly successful in the Visegrad countries, boosting their catching-up period and increasing these markets prosperity and competition levels. We look at the instruments governments and companies count on to consolidate foreign direct investment dynamics and to strength cooperation among international firms. We particularly consider the contributions of Johanson & Mattsson (1988), Hall & Soskice (2001) and Hadley & Wilson (2003). We find that the accessibility level that a new market represents for an investor shows some dependence on the stability and influence of corporate networks. We additionally conclude that incentive programmes proposed by governments have a limited role when contrasted to the processes described above.